Electrochemical immunoassay of antibodies using freshly prepared and aged conjugates of silver nanoparticles; Talanta; Vol. 253 - Dorozhko E. V. Elena Vladimirovna; Кazachinskaia E. I. Elena Ivanovna; Kononova Yu. Yulia; Zaikovskaya A.; Barek J. Jiri; Korotkova E. I. Elena Ivanovna; Kolobova E. N. Ekaterina Nikolaevna; Sheveleva P. A. Polina Aleksandrovna; Saqib M. Muhammad (2023, 2023)
Title screen